2022
DOI: 10.1039/d2ta06517g
|View full text |Cite
|
Sign up to set email alerts
|

Fast charge transfer between iodide ions and a delocalized electron system on the graphite surface for boosting hydrogen production

Abstract: Developing new catalysts to reduce the energy barrier for hydrogen production from water splitting has been an important research topic. It is well-known that the water-splitting voltage is limited by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…3f and g). 54 As shown in Fig. 3h, the polarization curves of the IOR, UOR, and OER, which have the potential to drive a current density of 20 mA cm −2 , are 1.30, 1.33, and 1.54 V RHE , respectively.…”
Section: Coupling Energy-saving Anodic Oxidation For Promoting Hydrog...mentioning
confidence: 92%
See 3 more Smart Citations
“…3f and g). 54 As shown in Fig. 3h, the polarization curves of the IOR, UOR, and OER, which have the potential to drive a current density of 20 mA cm −2 , are 1.30, 1.33, and 1.54 V RHE , respectively.…”
Section: Coupling Energy-saving Anodic Oxidation For Promoting Hydrog...mentioning
confidence: 92%
“…After extensive research, our group discovered that electrocatalysts could be easily synthesized from metal oxides, single atoms, and metal-free carbon materials, such as ruthenium-tin surface alloy oxide (RuSn SAO), 13 self-supporting RuTiO oxide alloy, 52 defective carbon-supported single-atom Mo-N 4 /d-C electrocatalyst, 53 and graphite-based carbon fiber paper (CFP). 54 These electrocatalysts have abundant active sites and a delocalized electron system which play an important role in the adsorption, activation, and desorption of iodide ions at the catalytic sites, which are favorable for the production of valuable iodine and green hydrogen energy at a lower operating voltage. Especially another major advancement in this field of research has been reported – a systematic approach to developing a RuTiO oxide alloy on 3D web-like titania via a hydrothermal route followed by a calcination process (Fig.…”
Section: Coupling Energy-saving Anodic Oxidation For Promoting Hydrog...mentioning
confidence: 99%
See 2 more Smart Citations